Circumstances, Resources, and Weight Status Outcomes Among Middle School Students. (November 2014) - Fitzpatrick, Kevin M.; Willis, Don; O'Connor, Gail
Obesity continues to plague U.S. school-age populations. A number of individual/structural circumstances have been identified as increasing the risk of poor health among children. The article's aim is to examine some of these circumstances and their relationship to students being overweight/obese, while highlighting resource variables as potential mediators to these negative circumstances. Using a sample of fifth- to seventh-grade students ( n = 334) attending a middle school in Northwest Arkansas, logistic regression models assessed the odds of students being overweight/obese compared with students of normal weight for their age and gender. Overall, students with higher depressive symptomatology and lower perceived social class were more likely (higher odds) to be overweight/obese. Students reporting higher levels of social and psychological resources were less likely (lower odds) to be overweight/obese; an inspection of changes in the circumstance's coefficients found once resources were introduced, resources appeared to play some mediating role in the final model.